1994
DOI: 10.1897/1552-8618(1994)13[109:eomomt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of Mixtures of Metals to the Zebra Mussel Dreissena Polymorpha

Abstract: The effects of equitoxic mixtures of CuCI,, ZnCI,, and CdCI, on the filtration rate of the freshwater mussel Dreissena polymorpha were determined. The amounts of added metals were expressed in toxic units, and a range of toxic units was tested. C u + Zn was less than concentration additive, Zn + Cd was concentration additive, and Cu + Cd was more than concentration additive in their effects on the filtratioil rate of Dreissenapolymorpha. An equitoxic mixture of all three metals was concentration additive. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
2
43
1
Order By: Relevance
“…Similar synergetic effects have been demonstrated in marine organisms; e.g. the combined effect of Cd, Cu, and Zn on zebra mussel Dreissena polymorpha (Kraak et al, 1994) and the Australian ghost shrimp Callianassa australiensis (Ahsanullah et al, 1981). In predicting effects in the field it is the combined effects that are of interest.…”
Section: The Toxicity Of Mixturesmentioning
confidence: 56%
“…Similar synergetic effects have been demonstrated in marine organisms; e.g. the combined effect of Cd, Cu, and Zn on zebra mussel Dreissena polymorpha (Kraak et al, 1994) and the Australian ghost shrimp Callianassa australiensis (Ahsanullah et al, 1981). In predicting effects in the field it is the combined effects that are of interest.…”
Section: The Toxicity Of Mixturesmentioning
confidence: 56%
“…Pb and Cd (e.g. SUNILA 1981, SIMKISS et al 1982, SIMKISS & MASON 1983, AMIARD et al 1987, KRAAK 1992, which are isolated in mineral granules or vacuoles and bound by low-molecule proteins, e.g. tioneine (for review see JURKIEWICZ-KARNKOWSKA 1994, 1998b (STAÑCZYKOWSKA & PLANTER 1985), the content of this element in molluscs from 1 m 2 bottom of the Zegrzyñski Reservoir was from over two to several times higher, and in the zebra mussel alone it was comparable.…”
Section: Filtration Activity Of Molluscs In Thementioning
confidence: 99%
“…IMLAY 1982, BALOGH 1988, BUSCH 1991, KRAAK et al 1991, KRAAK 1992, PEROVA 1996, OERTEL 1998, JAMIL et al 1999, JURKIEWICZ-KARNKOWSKA 1999b, GRUNDACKER 2000, though such studies are much less numerous compared to papers on marine habitats and only rarely pertain to dam reservoirs (e.g. JURKIEWICZ- KARN-KOWSKA 1999b, 2003, JURKIEWICZ-KARNKOWSKA & KRÓLAK 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the cumulative frequency distribution of the valve position of the individual mussels is less sensitive due to the high variability. It was also shown that the dosage experiments cannot be repeated on the same set of mussels due to strong adaptation effects [5].…”
Section: Evaluation Of the Dynamic Alarm System: Copper Experimentsmentioning
confidence: 99%
“…The valve movement response of freshwater (Dreissena polymorpha Pallas) and marine (Mytilus edulis) mussels has been used in monitoring studies [4][5][6][7]. The tissues of mussels can * To whom correspondence may be addressed.…”
Section: Introductionmentioning
confidence: 99%